VD_FINDINFO HC / 2012 / 78 vom 25. Januar 2012 - VD Tribunal cantonal (2012)
ASSISTANCE JUDICIAIRE, PROCÉDURE DE CONCILIATION, AVOCAT D'OFFICE | 117 CPC (CH), 118 al. 1 let. c CPC (CH), 121 CPC (CH), 202 CPC (CH)